Synthetic studies on glycosphingolipids from Protostomia phyla: total syntheses of glycosphingolipids from the parasite, Echinococcus multilocularis - Yamamura, Takeshi; Hada, Noriyasu; Kaburaki, Asuka; Yamano, Kimiaki; Takeda, Tadahiro (Carbohydrate research, 2004)
[Display omitted] Efficient and systematic syntheses of four neutral glycosphingolipids that have been isolated from the metacestodes of Echinococcus multilocularis have been achieved. A key step is the direct glycosylation of galactosyl donors using thioglycosides with benzoyl ceramide in the presence of N-iodosuccinimide (NIS)/TfOH, which gave the desired oligosaccharide derivatives. The fully protected glycosides 13, 20, 22 and 25 were deprotected to give four target glycosphingolipids ( 1– 4).